Therapeutic Potential of Synbiotic Roselle Extract Yogurt in Modulating Inflammatory Markers and Oral Microbiota in a Rat Model of 5-Fluorouracil-Induced Oral Mucositis - Sena, Anantha; Mudigdo, Ambar; Arief, Irma-Isnafia; Indarto, Dono (Bogor Agricultural University, Indonesia, 2026)
Mucositis is a common complication in cancer patients undergoing 5-fluorouracil (5-FU) chemotherapy. Roselle (Hibiscus sabdariffa) extract in synbiotic yogurt could be a beneficial alternative because it might change the inflammatory response and oral microbiota. The study aimed to investigate the effects of synbiotic roselle extract yogurt on inflammatory responses and oral microbiota in oral mucositis caused by 5-FU. An experimental study with twenty-four Sprague-Dawley rats divided into four groups (n=6): healthy control (NC), disease control (PC), synbiotic roselle extract yogurt therapy (P1), and standard therapy (P2) groups. This study evaluated the number of bacterial colonies, expression of COX-2 and caspase-1, and levels of IL-1β and VEGF (days 4 and 7). The P1 group had a significantly increased beneficial lactic acid bacteria (6.91±0.87) and a decrease in pathogenic bacteria, including Staphylococcus aureus (3.89±0.05), Escherichia coli (0), and Enterobacter aerogenes (1.78±0.29), compared to the PC group. Additionally, there was a statistically significant increase in VEGF levels in the tissue (0.07±0.03 ng/mL), a decrease in serum IL-1β levels (48.02±10.29 pg/mL), and an expression of caspase-1 and COX-2 compared to the PC group (p<0.05). Synbiotic roselle extract yogurt shows promise as a therapeutic strategy for managing mucositis by restoring microbial balance and mitigating inflammation.